2022
DOI: 10.3390/cancers14184362
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Ultra-Radical Surgery on Survival in Advanced Ovarian Cancer Using Population-Based Data in a Multicentre UK Study

Abstract: We investigated URS and impact on survival in whole patient cohorts with AOC treated within gynaecological cancer centres that participated in the previously presented SOCQER 2 study. National cancer registry datasets were used to identify FIGO Stage 3,4 and unknown stage patients from 11 cancer centres that had previously participated in the SOCQER2 study. Patient outcomes’ association with surgical ethos were evaluated using logistic regression and Cox proportional hazards. Centres were classified into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This cannot be compared to trial data or institutional figures which are subject to case selection bias. Our data is in keeping with population data both from the UK [43] and Nordic countries. In setting this target, the BGCS panel considered the fact that a proportion of individual Cancer Centres will have performance well above, as well as some below, the national mean intercept for Cancer Alliances.…”
Section: Best Practice Solutionsmentioning
confidence: 81%
“…This cannot be compared to trial data or institutional figures which are subject to case selection bias. Our data is in keeping with population data both from the UK [43] and Nordic countries. In setting this target, the BGCS panel considered the fact that a proportion of individual Cancer Centres will have performance well above, as well as some below, the national mean intercept for Cancer Alliances.…”
Section: Best Practice Solutionsmentioning
confidence: 81%
“…The ability of institutions to achieve optimal cytoreduction significantly differs worldwide, with an estimated range between 20% and 90% of cases [ 6 ]. The advances in surgical knowledge and expertise permit the completion of operations with a high surgical complexity score in our era [ 7 , 8 ]. When surgery is not considered feasible in terms of ensuring complete tumor resection, current consensus statements for ovarian cancer treatment state that neo-adjuvant chemotherapy should be provided, which must be followed by interval debulking surgery (IDS) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maximal cytoreductive surgery has recently been endorsed by NICE as standard treatment for patients with advanced OC [ 22 ]. This was following publication of the results from the prospective observational SOCQER-2 study showing no detrimental impact on QoL and improved survival in centres offering maximal-effort cytoreductive surgery [ 23 , 24 ]. Several studies have shown improved progression-free survival (PFS) and overall survival (OS) with maximal-effort cytoreductive surgery, but we do not know its impact on patients’ psychological morbidity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%